Length weight relationship and otolith morphometry of twelve species of sciaenids (Family: Sciaenidae) from Mumbai waters, India - Kumar, Pawan; Chakraborty, S. K.; Jaiswar, A. K.; Ali, Shahnawaz (Indian Journal of Fisheries, 2015)
Length-weight relationship of 12 fish species belonging to the family Sciaenidae landed at New Ferry Wharf, Sassoon Dock and Versova fish landing centers of Greater Mumbai were estimated between September 2006 and August 2007. A normal distribution of calculated ‘b’ values ranged from 2.3585 to 3.5458 and r2 values of length-weight relationship varied from 0.6356 to 0.9886. The Student’s t-test revealed that the b values significantly differed in 7 of the 12 species studied (p